Genetic Control and Breeding for Seed Size and Colour in Cowpea [Vigna Unguiculata (L.) Walp] - Egbadzor, K.F. (University of Ghana, 2014)
Consumer preference is very important in acceptance of an improved crop variety. Participatory rural appraisal (PRA) was therefore conducted on preferred traits of cowpea [Vigna unguiculata (L) Walp] among Ghanaian consumers in Ketu North, Ho and Akatsi districts. It was confirmed that the age long preference for large white cowpea among Ghanaian consumers still exists. Based on the results of the PRA, cowpea germplasm was assembled and used in genetic studies on seed coat colour and size. The total number of germplasm used for the various experiments was 126 from which 111 were from Ghana. Sixteen morphological traits were used in characterisation which clustered the improved varieties together indicating selection for similar traits. Molecular characterisation with 458 Single Nucleotide Polymorphic (SNP) markers clustered the germplasm based on seed coat colour and showed close relationship between improved varieties and materials from similar breeding programmes when analyzed with Darwin software. The software package structure was used to separate accessions into three groups, and the program correctly identified varieties that are known to have hybrid origins such as Zaayura and CB27. The SNP markers were also used in association mapping for cowpea seed size with Genstat statistical package. Eighteen of the SNP markers were observed to be highly associated with seed size and could be used in marker assisted selection for the trait. Eight of these 18 SNPs, one each located on Linkage Groups (LGs) 1, 5, 7, 10 and 11 and three on LG 4 were associated with both seed weight and thickness. Generation mean analysis (GMA) for seed size was conducted using CB27 and Gh3710 as the large and small seeded parents respectively. Results of the GMA analyzed with Genstat and SAS indicated that both fixable and non-fixable gene actions were important in seed size inheritance. Eight genes were estimated to control seed size of cowpea from the experiment. The broad and narrow sense heritability estimates were 84% and 35% respectively. Duplicate gene action was observed to control seed size inheritance in cowpea. Small seed size was partially dominant over large seed size. Seven genotypes were used in hybridization and the segregating populations used in seed coat colour inheritance study in cowpea. It was realized that segregation for seed coat colour could be complex resembling quantitative inheritance depending on the parental genotypes. It was therefore suggested that the use of quantitative and molecular approaches could help in better understanding of seed coat colour inheritance in cowpea. Participatory selection with farmers was done from six different F3 populations of cowpea from which four plants each were selected for further evaluation toward possible varietal development.
Thesis (PhD) - University of Ghana, 2014